Problem-solving with clinical reasoning: A case report of coronavirus in immunosuppressive condition - Mahshad Mousavi; Nazanin Mousavi; Babak Abdolkarimi (Tabriz University of Medical Sciences, 2021)
Background: One of the most interesting parts of medical science is using clinical reasoning to solve clinical problems. In today's world of medicine, with increasing amounts of scientific information and new diagnostic and treatment facilities, physicians' responsibility in managing the condition of patients becomes weightier. Making the correct decision is an important goal that can be achieved by having adequate information and using it appropriately. At this stage, we should follow the thought process of successful doctors and use information from books and articles to solve clinical problems. The purpose of this article is to improve the skills of physicians in the effective use of knowledge and experience to solve clinical problems to increase our success in fulfilling our responsibility to patients. Methods: Clinical reasoning enhances the quality of learning and increases the ability of medical students in clinical problem-solving. In this article, a patient with rheumatoid arthritis in the COVID-19 pandemic developed respiratory distress, is identified by the clinical reasoning method and is treated, with his treatment then discussed. This article includes the following: prepare a list of differential diagnoses based on the list of signs and symptoms of the patient; modify the initial list to reflect findings from history and examinations; specify additional information to make a correct diagnosis; and, finally, decide when the information is obtained is sufficient to make the proper diagnosis. Results: In recent years, clinical reasoning has received more attention in student Olympiad competitions. Professors in medical sciences should pay special attention to teaching this skill to students. It is necessary to plan for teaching this type of training and to design tests for evaluating students' clinical reasoning. This article can thus be a useful guide for those who enjoy working on a problem to get an answer. Conclusion: This article shows how insidious and life-threatening a coronavirus infection can be, and how useful clinical reasoning can be when present in all stages of dealing with the patient, from the initial stages of taking the patient history to the end of treatment.